'They just came with the medication dispenser'- a qualitative study of elderly service users' involvement and welfare technology in public home care services - Heidi Snoen Glomsås; Ingrid Ruud Knutsen; Mariann Fossum; Kristin Halvorsen (BMC, 2021)
Abstract Background Public home care for the elderly is a key area in relation to improving health care quality. It is an important political goal to increase elderly people's involvement in their care and in the use of welfare technology. The aim of this study was to explore elderly service users' experience of user involvement in the implementation and everyday use of welfare technology in public home care services. Method This qualitative study has an explorative and descriptive design. Sixteen interviews of service users were conducted in five different municipalities over a period of six months. The data were analysed using reflexive thematic analysis. Results Service users receiving public home care service are not a homogenous group, and the participants had different wishes and needs as regards user involvement and the use of welfare technology. The analysis led to four main themes: 1) diverse preferences as regards user involvement, 2) individual differences as regards information, knowledge and training, 3) feeling safe and getting help, and 4) a wish to stay at home for as long as possible. Conclusion The results indicated that user involvement was only to a limited extent an integral part of public home care services. Participants had varying insight into and interest in welfare technology, which was a challenge for user involvement. User involvement must be facilitated and implemented in a gentle way, highlighting autonomy and collaboration, and with the focus on respect, reciprocity and dialogue.